SOSYAL İNOVASYONUN MARKA İMAJINA OLAN ETKİSİ - TOPRAK, CESUR (Fırat Üniveristesi, 2018)
Bilginin ekonomik güç kazandığı günümüzde; hızla gelişen teknoloji beraberinde üretim, tüketim ve pazarlama alanlarında da değişimlere yol açmıştır. Özellikle değişen tüketici davranışları firmaları yeni stratejiler geliştirmeye zorlamıştır. Günümüzde firmalar, hem tüketicilerin isteklerini ve ihtiyaçlarını karşılayarak onların tatmin edilmesine odaklanmakta hem de sosyal sorumluluk bilinciyle toplumun gereksinimlerine cevap vermeye çalışmaktadırlar. Tüketiciler satın alma kararını verirken birini diğerlerine tercih etmek zorunda kalmaktadır. Artan ürün çeşitliliği karşısında tüketicinin kararını etkileyen yalnızca ürünün özellikleri olmamaktadır. Tüketicilerin satın alma kararı vermelerinde firmaların sosyal sorumluluk faaliyetlerine yönelik algıları ve tutumları da olukça önemlidir. Böylece tüketicilerin bu uygulamalara yönelik olumlu tutumları firmalara farklı bir rekabet üstünlüğü sağlamaktadır. Bu çalışmada Turkcell firmasının sosyal sorumluluk bilinciyle gerçekleştirdiği inovasyonu tema alan kamu spotu ele alınmıştır. Bu çerçevede katılımcıların söz konusu kamu spotuna verdiği tepkiler ölçülmeye çalışılmıştır. Araştırmada; Turkcell' in sosyal inovasyon temalı kamu spotu EEG Analiz Yöntemi kullanılarak incelenmiş ve 30 gönüllü katılımcı ile gerçekleştirilmiştir. Elde edilen bulgulara bakıldığında; gönüllü katılımcıların söz konusu kamu spotundan etkilendiği belirlenmiştir. Diğer bir ifadeyle, Turkcell'in bu kamu spotunu kullanarak marka imajını güçlendirdiği görülmüştür.

Nowadays, when knowledge acquired economic capacity; rapidly developing technology has led to island changes in the fields of production, consumption and marketing. Particularly changing consumer behavior has forced firms to develop new strategies. Nowadays, companies focus on satisfaction of consumers by meeting their demands and needs and also try to respond to society's needs with the awareness of social responsibility. Consumers have to choose one of them when they make a purchase decision. There is no everyday product characteristic that affects the consumer's decision in the face of increasing product variety. The perception and attitudes of the companies in their social responsibility activities are also important for the consumers to make purchasing decisions. This is because the consumer has a different competitive advantage in operating positive attitudes towards these applications. In this study; a public spot on the preparation of birthday gift of mother of visually impaired student in 80 class which Turkcell company established for visually impaired students with social responsibility consciousness was handled. In the study, when Turkcell company presented the innovation that it made in the social awareness stage as a public spot, it tried to measure the reactions that consumers responded to the spot. In the study; Turkcell's social innovation was examined using the public spot EEG analysis method. The research was conducted with 30 volunteer participants. Volunteer participants were watched Turkcell's public spot with social innovation theme and at the same time participant's brain activations were recorded with the EEG Analysis Method which is one of the neurometry methods. Participants' responses to public spots were compared with the results of the EEG Analysis method. According to the findings obtained; it has been determined that volunteer participants are affected by the public spots in question. In other words, it has been determined that Turkcell's image is strengthened with the public spot.
The impact of social innovation on brand image
Keywords: İşletme